Physiopunk Vol 1 - Maric (PhD), Filip; Nikolaisen, Liv Johanne; Bårdsen, Åse (OpenPhysio Journal, 2021)
Physiopunk emerged out of an introductory public health module for first-year students in the Bachelor program in physiotherapy at UiT The Arctic University of Norway. Throughout the module, students gradually expanded their view of physiotherapy, from its past and present individual and physical health focus toward the integration of social and ecological issues as fundamental determinants of health. Because considering and addressing social and ecological issues is still a novelty in physiotherapy that will require considerable innovation and transformation, students were finally invited to conclude their learning by writing fictional stories about diverse futures for physiotherapy.